2022
DOI: 10.3390/foods11233790
|View full text |Cite
|
Sign up to set email alerts
|

Gluten-Free Product Contribution to Energy and Macronutrient Intakes in Spanish Children and Adolescents with Celiac Disease

Abstract: Gluten-free products (GFP) are a good choice for the replacement of cereals when following a gluten-free diet due to celiac disease (CD). However, commercial GFP are made with highly refined flours and may contain more fat, sugar, and salt, and less fiber and micronutrients than gluten-containing analogues, thus challenging the nutritional adequacy of the diet. The aim of this study is to assess the contribution of GFP to the diets of children and adolescents with CD. Food intakes were assessed in a cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In most studies, it was reported that there were significant increases in total fat and saturated fatty acid intake of children with celiac disease than the control group (Babio et al, 2017;Balamtekin et al, 2015;Ferrara et al, 2009;Kautto et al, 2014;Zuccotti et al, 2013). In a Spanish study, gluten-free diet contributed with a high percentage (>25%) to total energy, carbohydrates, fiber, and salt intakes (González et al, 2022). Moreover, ultra-processed food consumption was shown to increase in diet (Martín-Masot et al, 2022).…”
Section: Discussionmentioning
confidence: 96%
“…In most studies, it was reported that there were significant increases in total fat and saturated fatty acid intake of children with celiac disease than the control group (Babio et al, 2017;Balamtekin et al, 2015;Ferrara et al, 2009;Kautto et al, 2014;Zuccotti et al, 2013). In a Spanish study, gluten-free diet contributed with a high percentage (>25%) to total energy, carbohydrates, fiber, and salt intakes (González et al, 2022). Moreover, ultra-processed food consumption was shown to increase in diet (Martín-Masot et al, 2022).…”
Section: Discussionmentioning
confidence: 96%
“…Pseudo-cereals such as amaranth, buckwheat, and quinoa, but also milled legumes, seeds, and nuts, are optional ingredients increasingly used for the preparation of gluten-free baked goods compared to GCCs [ 54 , 56 , 64 ], which enlarge the quantity of fibre of the GFPs. Nevertheless, despite the higher fibre content of GFPs, people following a strict GFD have a lower fibre intake than the rest of the population if the intake of the whole day, not only for breakfast, is assessed [ 27 , 36 , 45 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of products marketed as gluten-free indicates that most of them have a higher salt content, especially breads, pastries, and cakes, compared to GCCs [ 44 , 71 , 72 ]. Salt reduction in cereal-based products for celiacs is another important issue to be addressed by the food industry, as we have previously proposed [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation